The Business Model Canvas - Alan Murray; Veronica Scuotto (Symphonya, 2016)
With global and local markets being transformed by the new techno-culture of digital and social technologies, more and more entrepreneurs need to be guided through their entrepreneurial journey. Whilst the management literature declares that there are numerous widely recognised tools available which the entrepreneur can use to help build or develop their business model in order to keep abreast of technological changes such as the business plan, lean start up and experimental lab, we propose that the Business Model Canvas (BMC) is a better fit for the market - orientated entrepreneur. This paper applies the Business Model Canvas to a single case study in order to investigates how a real entrepreneur relies on the nine blocks of the BMC namely; value proposition, key activities, key resources, cost structure, key partners, customer relationships, customer segments, channels, and revenue streams.